2-[(2,4,6-Trimethylbenzene)sulfonyl]phthalazin-1(2H)-one: crystal structure, Hirshfeld surface analysis and computational study - Izuogu, D. C.; Asegbeloyin, J. N.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2020)
The X-ray crystal structure of the title phthalazin-1-one derivative, C17H16N2O3S {systematic name: 2-[(2,4,6-trimethylbenzene)sulfonyl]-1,2-dihydrophthalazin-1-one}, features a tetrahedral sulfoxide-S atom, connected to phthalazin-1-one and mesityl residues. The dihedral angle [83.26 (4)°] between the organic substituents is consistent with the molecule having the shape of the letter V. In the crystal, phthalazinone-C6-C—H...O(sulfoxide) and π(phthalazinone-N2C4)–π(phthalazinone-C6) stacking [inter-centroid distance = 3.5474 (9) Å] contacts lead to a linear supramolecular tape along the a-axis direction; tapes assemble without directional interactions between them. The analysis of the calculated Hirshfeld surfaces confirm the importance of the C—H...O and π-stacking interactions but, also H...H and C—H...C contacts. The calculation of the interaction energies indicate the importance of dispersion terms with the greatest energies calculated for the C—H...O and π-stacking interactions.